2017
DOI: 10.1080/10408398.2015.1063478
|View full text |Cite
|
Sign up to set email alerts
|

Evidences and perspectives in the utilization of CLNA isomers as bioactive compounds in foods

Abstract: Conjugated alpha linolenic acid (CLNA) isomers are promising lipids owing to their similarities with conjugated linoleic acid (CLA) but exerting their bioactivity at lower doses; some isomers also belong to omega 3 family. This review aims to summarize the state of the art about the utilization of CLNA as a functional ingredient. Indeed, in vitro and in vivo studies reported that CLNA exerted anticancer, anti-inflammatory, anti-obese, and antioxidant activities. However, CLNA has not been tested in humans. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 101 publications
0
38
0
2
Order By: Relevance
“…Regarding CLNA isomers, their effects have been reviewed as being associated with anticancer, anti-inflammatory, antioxidant, and antiobesity activities (16,17).…”
Section: Cla and Clna Bioactivitymentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding CLNA isomers, their effects have been reviewed as being associated with anticancer, anti-inflammatory, antioxidant, and antiobesity activities (16,17).…”
Section: Cla and Clna Bioactivitymentioning
confidence: 99%
“…Accordingly, it was concluded that ruminal microbes are capable of transforming LNA into both CLA and 18:3 compounds. Finally, these intermediates are then hydrogenated into stearic acid (C 18:0 ) (17,26), and fatty acids are absorbed in the gut and transported via the bloodstream to different body tissues (27,28).…”
Section: Cfa and Rumen Biohydrogenationmentioning
confidence: 99%
See 1 more Smart Citation
“…CFAs production by dairy propionibacteria is a way to cope with the inhibitory effect of fatty acids on bacterial growth [88]. Dairy propionibacteria, such as P. freudenreichii , produce the isomer cis-9, trans-11 octadecadienoic (Rumenic acid, RA) in culture and in fermented dairy products from LA; and isomerize also the c12-double bond of LNA and γ-linolenic acid [84,85,87,89]. Nonetheless, animals and clinical studies report the anti-inflammatory effects of CLA and CLNA including those produced by dairy propionibacteria, at different level of modulation, according to isomer type, by acting as PPARγ agonists.…”
Section: Immunomodulation By Dairy Propionibacteriamentioning
confidence: 99%
“…In vitro and in vivo studies showed the anti-proliferative effect of conjugated fatty acids, including those produced by dairy propionibacteria [84,86,87,88,89], on various cancerous cells such as melanoma, colorectal, breast, prostate and hepatoma cell lines [92]. The anti-proliferative kinetic is time and dose dependent.…”
Section: Anti-cancerous Effectmentioning
confidence: 99%